A Review on Unani Management of Amraz e Qalb: Naazneen M.N.F.* and Salma M.L.U. (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
One of the body's essential organs is the heart, also referred to as Qalb. The Unani system of medicine defines the cardiac diseases under Amraz e Qalb. All over the world, cardiovascular diseases (CVDs) account for the foremost cause of mortality. Regardless of developing and non-developing countries CVDs cause a greater burden of disease. Unani scholars gave the utmost important to every facet of the treatment of Amraz e Qalb. Effective principles of treatment to be followed have been recorded along with effective Mufrad vo Murakkab Advia (Single and compound medicines), Ilaj bil Tadbeer (Regimenal therapies) and, Hidayat (Advice). The study is aimed at compiling those effective regimes paying particular attention to the drugs that have shown potent cardioprotective activity. Authentic Unani text books, and pharmacopoeias were reviewed to get information on Amraz e Qalb and its management. A search of scientific journals and research articles was conducted to determine the cardioprotective activity of the commonly given medications. There are sufficient natural medications to adequately treat CVDs. While more scientific research needs to be conducted in the future, this study has provided a significant quantity of information on the management of Amraz e Qalb that might be used for the successful treatment of CVDs